RADON IN WATER FROM PRIVATE WELLS AND ITS CONTRIBUTION TO INTERNAL EXPOSURE OF POPULATION IN RURAL AREAS AT TOPLICA REGION, SOUTHERN SERBIA - Vučković, Biljana; Penjišević, Ivana; Todorović, Nataša; Nikolov, Jovana; Radovanović, Dragan; Valjarević, Aleksandar (Bulletin of Natural Sciences Research, 2024)
The results presented in this paper are part of the investigating of radon the concentrations from natural sources in the Toplica region. The results refer only to the radon concentrations in water from private captured wells at 12 locations. Radon concentration in water was measured by alpha spectrometry using the RAD 7 – RAD H2O system. The range of radon concentration is from (2.8±1.2) to (76.0±4.0) kBq/m3, and the contribution of radon released from water to the air in the premises was in range (0.8±0.3) to (22.8±1.2) Bq/m3. The annual effective doses of inhaled and ingested radon were determined, the mean values were (114.8±14.8) and (3.2±0.3) μSv/y.